HUBUNGAN PENGETAHUAN DAN SIKAP TERKAIT LABEL PANGAN DENGAN KEPATUHAN MEMBACA LABEL PANGAN PADA MAHASISWA UNIVERSITAS DIPONEGORO - Nisa, Lainatin; Nuryanto, Nuryanto; Purwanti, Rachma; Dieny, Fillah Fithra (Department of Nutrition Science, Faculty of Medicine, Universitas Diponegoro, 2024)
ABSTRACTBackground: The label on the food packaging contains the content, type, nutrients information, expiration date and other important informations. Reading food labels will affect the consumer in selecting the food products in the market. This study aimed to determine the relationship between the level of knowledge and attitudes toward compliance with reading food labels in college students.Methods: This study was designed using a cross-sectional survey. The consecutive sampling method is used in selecting the subject. Research data was obtained by sending research questionnaires to 106 Diponegoro University students and conducted between May and June 2022. The research data was obtained using a questionnaire that included questions about demographic characteristics, level of knowledge about nutrition and food labels, attitudes towards food labels, and level of adherence to reading food labels. Data then analyzed by a bivariate correlation test using Spearman's rank correlation.Result: There is a significant correlation between knowledge about nutrition labels and attitudes towards food labels (p=0.019), as well as attitudes towards food labels and reading food labels compliance (p<0.001). There is no significant correlation between knowledge and compliance to reading food labels (p=0.26). Reading food labels compliance is influenced by attitudes, age of respondents, and expenditure on food.Conclusion: Reading food labels compliance relates with attitudes, respondent’s age, and expenditure on food. Knowledge about nutrition label relates with the attitudes towards food labels.Keywords: food label, knowledge, attitude, compliance ABSTRAKLatar belakang: Label pangan berisi tentang informasi mengenai komposisi, nilai zat gizi, jenis, tanggal kadaluarsa dan keterangan penting lainnya. Kebiasaan membaca label pangan akan mempengaruhi keputusan seseorang dalam membeli makanan yang akan dikonsumsi. Penelitian ini bertujuan untuk menganalisis hubungan pengetahuan dan sikap terkait label pangan dengan kepatuhan mahasiswa Universitas Diponegoro dalam membaca label pangan.Metode: Desain penelitian cross sectional dengan jumlah subjek 106 mahasiswa Universitas Diponegoro, berlangsung pada bulan Mei-Juni 2022. Metode pengambilan subjek dengan consecutive sampling. Data penelitian diperoleh dengan menggunakan kuesioner yang meliputi pertanyaan mengenai karakteristik demografis, tingkat pengetahuan, sikap terhadap label pangan, dan kepatuhan membaca label pangan. Analisis bivariat dengan uji korelasi spearman.Hasil: Terdapat hubungan antara pengetahuan tentang label pangan dengan sikap terhadap label pangan (p=0,019), serta sikap terhadap label pangan dan kepatuhan membaca label pangan (p<0.001). Tidak terdapat hubungan antara pengetahuan tentang label pangan dan kepatuhan membaca label pangan (p=0,26). Kepatuhan membaca label pangan dipengaruhi oleh sikap, usia responden, dan pengeluaran untuk pangan.Simpulan: Kepatuhan membaca label pangan berhubungan dengan sikap, usia responden, dan pengeluaran untuk pangan. Pengetahuan tentang label pangan berhubungan dengan sikap terhadap label pangan.Kata kunci : pengetahuan, sikap, kepatuhan, label pangan